Testing a Neuro-Evolutionary Theory of Social Bonds and Addiction: Methadone Associated With Lower Attachment Anxiety, Comfort With Closeness, and Proximity Maintenance - Torres, Nuno (Frontiers in Psychiatry, 2019)
Evidence from non-human mammals for the involvement of the endogenous opioid system in prosocial behavior is reasonably extensive and robust; however, studies in humans are lacking. This study tests the neuro-evolutionary hypothesis that exogenous opiates, including morphine, heroine, and methadone, decrease separation anxiety and proximity by hijacking the neuro-peptide endogenous opioid system modulating social bonds. Participants were 486 subjects, 43% male, with ages between 18 and 62 years (M = 26.4; SD = 9.4), divided in three naturalistic groups: 1: addicts in drug-free treatment; 2: addicts in methadone programs; 3: normative non-clinical controls. Instruments: 1) Adult Attachment Scale (AAS) composed of three subscales: Anxiety about being rejected (α = 0.83), Comfort with Intimacy (α = 0.68), and Comfort Depending on Others (α = 0.70). 2) Caregiving Questionnaire composed of four subscales: Proximity Maintenance: (α = 0.83), Sensitivity: (α = 0.76), Controlling Caregiving (α = 0.77) and Compulsive Caregiving (α = 0.68). Results: Multivariate Analysis of Co-variance (MANCOVA) models were computed; gender, age, and education were included in the models. Methadone patients and drug-free treatment addicts were equivalent and reported significantly lower Comfort Depending on Others, Comfort with Intimacy, and Caregiving Proximity. However, methadone users reported significantly lower Anxiety about being rejected than drug-free addicts and were equivalent to non-clinical controls. In addition, correlations between the methadone intake dose and the questionnaires’ scales showed that dose was significantly and negatively correlated with Comfort with Closeness (rs = −0.36; p < 0.01) and with Caregiving Proximity (rs = −0.28; p < 0.05).